Covalent Organic Framework as an Efficient Protection Layer for a Stable Lithium‐Metal Anode. (2nd March 2022) - He, Jiarui; Bhargav, Amruth; Manthiram, Arumugam
Abstract: Lithium (Li) metal shows great potential for achieving high‐energy‐density rechargeable batteries. However, the practical applications of Li‐metal batteries are still challenged by the formation of Li dendrites and unstable solid‐electrolyte interphase (SEI) on metallic Li. Herein, a thin covalent organic framework layer is in situ fabricated on Li (COF‐Li) to suppress Li dendrite growth and mitigate the side reaction on the Li anode. The COF has a periodic and uniform porosity, allowing for selectively sieving Li ions and guiding a uniform Li deposition. As a result, the COF‐Li exhibits a non‐dendrite morphology during repeated Li plating/stripping and demonstrates a remarkable cycle life over 13 200 h with an extremely low overpotential of only 16 mV at a high current density of 10 mA cm −2 and a high areal capacity of 10 mAh cm −2 . Abstract : A thin covalent organic framework layer is in situ fabricated on Li (COF‐Li) to suppress Li dendrite growth and mitigate side reactions on the Li anode. COF‐Li exhibits a non‐dendritic morphology during repeated Li plating/stripping and demonstrates a remarkable cycle life of >13 200 h with an impressive low overpotential of 16 mV at a high current density of 10 mA cm −2 and a high areal capacity of 10 mAh cm −2 .